Caracterização da Matéria Orgânica Dispersa através da técnica de Pirólise "Rock-Eval II" Vantagens e Limitações para a Geologia - ADE, MARCUS VINICIUS BERAO (Pesquisas em Geociências, 2000)
The development of Rock-Eval II pyrolysis technique in the end of 70’s, offered a very important tool for disperse organic matter study. Rock-Eval II pirolysis of whole rock has been used by geologist to identify the type, quantity and thermal maturity of organic mailer associated with sedimentary rocks. It is fast and inexpensive method to evaluate petroleum-generation potential and organic metamorphism of rocks. This technique allows obtention of repeatable data, very important determining stratigraphic and geographic extent of occurrence of source rock. However pyrolysis is results must be carefully analised to avoid misunderstanding, regarding, for example, altered sample. interference of clay-minerals associated with organic matter, the kerogen type, imature sediments etc., can lead to mistaken interpretation.